5 Sola Reformation. Theological principles of heterogenious protestantism - Serhii Sannіkov (Cхід, 2017)
The paper displays the religious and theological foundations, which initiated the reformation process with the help of nowadays popular markers known as 5 Sola of Reformation. It demonstrates the main theological principles which identify Protestantism among other religious groups. But simultaneously the hermeneutics of these principles divides Protestantism into many currents, which forms this religious movement heterogeneity. The main focus of the article lays on the comparative description of each of five features of the theological system of Reformed theology in the understanding of masters and radical reformation. The history of formation of 5 Sola and its theological meaning are analyzed as well.